The effect of occupational therapy in patients with chronic obstructive pulmonary disease: A randomized controlled trial. (4th March 2017) - Martinsen, Unni; Bentzen, Hege; Holter, Morag Kelly; Nilsen, Tove; Skullerud, Hallvard; Mowinckel, Petter; Kjeken, Ingvild
Abstract: Aim The main aim of this study was to evaluate the effect of individualized occupational therapy in patients with chronic obstructive pulmonary disease (COPD). Additionally, the authors wanted to explore the occupational problems experienced in daily life by individuals with COPD.Methods A total of 52 patients were randomly assigned to the intervention group (occupational therapy) or control group (treatment as usual). The primary outcome was assessed using the Canadian Occupational Performance Measure (COPM), and participants were assessed at baseline and after four and 12 months.Results There were no treatment effects on occupational performance or satisfaction with performance, as measured by the COPM. However, we found a significant effect in favour of the intervention group at exertion when performing an individually chosen activity, and in the activity dimension of St George's Respiratory Questionnaire. A total of 595 occupational problems were reported, most frequently within mobility, active recreation, and household management.Conclusions The results show that, compared with the usual care, individualized occupational therapy did not improve occupational performance or satisfaction with performance. Small but significant changes in activity performance in favour of the intervention group were found in some of the secondary outcomes.